L’éducation aux médias : contributions, pratiques et perspectives de recherche en sciences de la communication - Normand Landry; Joëlle Basque (Communiquer)
This article defines media education as both a field and a privileged object of study, particularly focusing on the implementation of critical perspectives from communication and education studies. In this regard, it synthesizes and problematizes the theoretical landscape of media education and identifies its specificities, goals and issues. In addition, the article discusses critically the concept of “media literacy” as the main theoretical proposition of media education. Finally, while highlighting problems associated with elements of media literacy, the article suggests avenues to guide research into the coming years. It thus aims to position media education as crucial to communication studies and makes explicit its contributions to the discipline.